Innovative Teaching of Building Technology to Architecture Students in Malaysia - S P Rao; Ezrin Arbi (Journal of Design and the Built Environment, 2006)
Architecture teaching involves not only the teaching of art and aesthetics but also the science of building. With the increased use of high-rise construction, intelligent building features as well as the use of Building Services to make the buildings habitable, it becomes imperative that the students of architecture understand and appreciate the complexities of the engineering systems to make the buildings sustainable and energy efficient. The process of Architecture design starts with the sketch design by the architect. At this point, many major decisions are being made with respect to the orientation, fenestration, service cores, environmental control systems etc. These preliminary design decisions would affect the overall energy efficiency of the building as such. It is thus necessary for the architecture student to comprehend and assimilate advanced building technologies. This paper presents a novel approach adopted in the Department of Architecture at the University of Malaya, commencing from the academic session 2005-2006 for the teaching of Advanced Building Technology to Year 4 students.